The Trail of Tears - Birchfield, D. L., 1948- (World Almanac Library, 2004)
Describes the history of the five tribes of Southeastern America, the Cherokee, Chickasaw, Choctaw, Creek, and Seminole, especially their forcible removal in the 19th century to the Great Plains.